LITAO3 CHARACTERIZATION OF RUBIDIUM ON TEMPERATURE VARIATIONS - Agus Ismangil; Teguh Puja Negara (Journal of Science Innovare, 2018)
One of the studies that recently attracted the attention of physicists is research on ferroelectric material because this material is very promising for the development of new generation devices in connection with the unique properties it has. Ferroelectric materials, especially those based on a mixture of lithium tantalite (LiTaO3), are expected to be applied to the infrared sensor. Lithium tantalate (LiTaO3) is a ferroelectric material that is unique in terms of pyroelectric and piezoelectric properties that are integrated with good mechanical and chemical stability. Therefore LiTaO3 is often used for several applications such as electro-optical modulators and pyroelectric detectors. LiTaO3 is a non-hygroscopic crystal, colorless, soluble in water, has a high transmission rate and does not easily damage its optical properties. LiTaO3 is a material that has a high dielectric constant and a high load storage capacity. This research has succeeded in determining the band gap energy of the LiTaO3 film in the rubidium chamber obtained in the range of values 2.02-2.98 eV as shown in figure 4. The LiTaO3 film after the annealing process at a temperature of 650 oC, has the highest band gap energy of 2.98 eV. Large energy is needed on the electrons to be excited from the valence band to the conduction band. Whereas in the LiTaO3 film after an annealing process of 800 oC, the band gap energy obtained is 2.02 eV. This makes it easier for electrons to be excited from the valence band to the conduction band because the energy needed is not too large.